PENGARUH BOARD INDEPENDENCE, PROFITABILITY, LEVERAGE, FIRM SIZE, AUDIT COMMITTEE TERHADAP INCOME SMOOTHING - Jason Christopher; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to examine empirically the effect of board independence, profitability, leverage, firm size and audit committee on income smoothing in manufacturing companies listed in the Indonesia Stock Exchange for the period 2017-2019. Sample was selected using purposive sampling method and data used was 75 companies. The test method used in this study was binay logit using EViews 10 software. Based on the results of the research that was done, it could be concluded that profitability, leverage and firm size had a negative effect on income smoothing, meanwhile board independence and audit committee had no effect on income smoothing. The implication of this research was the need to increase the awareness of investors regarding company profits that look good and all the information presented in the financial statements in order to be free from management manipulation or income smoothing.